Upaya Meningkatkan Pemahaman Konsep Fisika Kelas X-1 Melalui Pembelajaran Kontekstual Di SMAN 1 Sinunukan - Indra Bahri,; Eni Sumanti Nasution; Nurhasana Siregar (Universitas Gara Nusantara Padangsidimpuan, 2024)
This research uses classroom action research. The stages are planning, implementation, observation and reflection. This activity uses data collection instruments through tests of students' understanding of physics concepts. The population used was students of SMAN 1 Sinunukan and the sample used was class X1 students with a total of 30 students. The data analysis technique uses the average value and student learning completeness value from pre-cycle, cycle I and cycle II. The results of the research concluded that there was a difference in understanding of physics concepts using the CTL learning model through pre-cycle, cycle I and cycle II and in cycle II it reached above the KKM of